Health Promotion to Increase Knowledge and Skills of Posyandu Cadres in Stimulating Toddler Development - Sadiman Sadiman; Islamiyati Islamiyati (Peneliti Teknologi Teknik Indonesia, 2022)
Posyandu is a community health center extension that provides integrated health services and monitoring undertaken by and for the benefit of the community. Posyandu cadres interact with the community the most, giving them a strategic advantage and an effective platform to spread health-related messages. Good cadre skills are required for this so that they can motivate the community in their working areas. The study discovered that 55.3% of Posyandu cadres in Saptomulyo Village lacked knowledge, and 65.9% lacked skills in stimulating toddler growth and development. This problem can be solved by promoting health through training, specifically through additional material distribution with demonstrations and practices. Cadres performing stimulation at their respective posyandus are assessed directly. Community service results revealed that ten cadres (41.47%) had very poor, and three (12.50%) had very good knowledge scores. Two people received the lowest post-test score, 8.33%, while sixteen received the highest score, excellent, 66.67%. The average pre-test score is 5.72, with a 2.94-point increase to the average post-test score of 8.67. According to the post-program evaluation, six cadres had lower skill scores, twelve had sufficient skill scores, and six had good skill scores, with no very poor or very good scores. It is suggested that the Saptomulyo Village apparatus keep monitoring cadre activities and providing complete infrastructure facilities for stimulating toddler growth and development.